When did the Statue of Liberty turn green? : and 101 other questions about New York City - Ashton, Jean; Nazionale, Nina (Columbia University Press, 2010)
For years, the librarians at the New-York Historical Society have kept a record of the questions posed to them by curious New Yorkers and visitors to the city. Who was the first woman to run for mayor of New York? Why are beavers featured on the city's official seal? Is it true that a nineteenth-century New Yorker built a house out of spite? These questions involve people, places, buildings, monuments, rumors, and urban myths. They concern sports, food, transportation, the arts, politics, nature, and Central Park, among many other subjects. Taken together, they attest to the infinite stories hidden within the most intriguing metropolis in the world. In When Did the Statue of Liberty Turn Green? the staff of the New York Historical Society Library answer more than a hundred of the most popular and compelling queries. The endlessly entertaining entries in this book feature hard-to-find data and unforgettable profiles, sharing snapshots of New York's secret history for all to enjoy. Drawing on the library's extensive collections, the staff reveal when the first book was printed in New York, whether the story of Harlem residents presenting rats to government officials is true, who exactly were the Collyer brothers and why were they famous, and why premature babies were once displayed in Coney Island. For readers who love trivia, urban history, strange tales, and, of course, New York City, this book will delight with its rich, informative, and surprising stories.--